Efektivitas Madu dan Tablet Fe Terhadap Peningkatan Kadar Hemoglobin Pada Ibu Hamil Trimester II dengan Anemia Ringan di PMB E Kecamatan Cikeusik Kabupaten Pandeglang Banten - Eva Widayati Khoiriyah; Gaidha Khusnul P (Universitas Malahayati Lampung, 2024)
ABSTRACT WHO reports that the prevalence of pregnant women worldwide who experience anemia is 41.8%. Prevalence among pregnant women varies from 31% in South America to 64% in southern Asia. South and Southeast Asia combined also contributes up to 58% of the total population experiencing anemia in developing countries. in North America, Europe and Australia it is rare to experience anemia due to iron deficiency during pregnancy. Even in the US only about 5% of young children and 5-10% of women of childbearing age suffer from anemia due to iron deficiency. Providing midwifery care and knowing the effectiveness of honey and FE tablets on increasing hemoglobin levels in second Trimester pregnant women with mild anemia in PMB E, Cikeuisk sub-district, Pandeglang district in 2023. This research is a quantitative research with a case study design with an experimental approach and the samples used were pregnant women in the second period who experienced mild anemia. Which provides intervention for 14 days. There was a difference in the increase in hemoglobin levels when given honey and Fe increased by 1.7 g/dl and Fe tablets increased by 0.9 g/dl. Pregnant women who were given the intervention of giving Honey experienced an increase in hemoglobin levels more quickly compared to pregnant women who were given the intervention of giving Fe Tablets. It is hoped that the community, especially pregnant women, can implement the use of Honey to prevent anemia. Keywords: Anemia, Pregnant women, FE Tablets, Honey ABSTRAK WHO melaporkan bahwa prevalensi ibu hamil di seluruh dunia yang mengalami anemia sebesar 41,8%. Prevalensi di antara wanita hamil bervariasi dari 31% di Amerika Selatan hingga 64% di Asia selatan. Gabungan Asia Selatan dan Tenggara juga berkontribusi hingga 58% dari total populasi mengalami anemia di negara berkembang. di Amerika Utara, Eropa dan Australia jarang mengalami anemia karena kekurangan zat besi selama kehamilan. Bahkan di AS hanya sekitar 5% anak kecil dan 5-10% wanita usia subur yang menderita anemia akibat defisiensi besi. Memberikan asuhan kebidanan dan mengetahui efektivitas Madu dan tablet FE terhadap peningkatan kadar hemoglobin pada ibu hamil Trimester II dengan anemia ringan di PMB E kecamatan Cikeuisk kabupaten pandeglang tahun 2023. Penelitian ini merupakan penelitian kuantitatif dengan rancangan studi kasus dengan pendekatan eksperimen dan sampel yang digunakan adalah ibu hamil timester II yang mengalami anemia ringan. Yang berikan intervensi selama 14 hari. Terdapat perbedaan peningkatan kadar hemoglobin yang di berikan madu dan Fe meningkat 1.7 g/dl dan Tablet Fe meningkat 0.9 g/dl. Ibu hamil yang diberikan intervensi pemberian Madu lebih cepat mengalami peningkatan kadar hemoglobin dibandingkan dengan ibu hamil yang diberikan invervensi pemberian Tablet Fe Diharapakan masyarakat khususnya ibu hamil dapat mengimplementasikan, penggunaan Madu terhadap pencegahan anemia. Kata Kunci: Anemia, Ibu Hamil, Tablet FE, Madu